Effect of concurrent training on trainability performance factors in youth elite golf players - Redondo, J. C.; de Benito, A. M.; Izquierdo, J. M. (PeerJ, 2020)
Background: Due to the early specialization of golf players, examining the within session sequence of training should be considered to enhance performance and prevent injury risk. The present study analyzed the effects of an 18-week concurrent training developed before or after a specific golf session in adolescence elite golfers on several performance factors.